Digital Wings: Innovations in Transplant Readiness for Adolescent and Young Adult Transplant Recipients. Issue 10 (October 2019) - Mogul, Douglas B.; Fredericks, Emily M.; Brady, Tammy M.; Miloh, Tamir; Riekert, Kristin; Williams, Natalie; Ford, Ryan; Fergusson, Michael; Kosmach-Park, Beverly; Hochstein, Jon; Naraparaju, Gayathri; Henderson, Macey L.; et al.
Abstract : The Johns Hopkins University School of Medicine organized 2 multistakeholder symposia on February 2, 2018 and January 11, 2019 to address the problem of high graft failure in adolescent and young adult (AYA) solid organ transplant (SOT) recipients. Participants included international experts in transplantation, behavioral psychology, patient/parent advocacy, and technology. The objectives of the symposia were as follows: (1) to identify and discuss the barriers to and facilitators of effective transfer of care for AYA SOT recipients; (2) to actively explore strategies and digital solutions to promote their successful transfer of care; and (3) to develop meaningful partnerships for the successful development, evaluation, implementation, and dissemination of these digital solutions. Additionally, data were collected from 152 AYA SOT recipients demonstrating a substantial gap in how this population uses technologies for health-related activities, alongside an increased interest in an app to help them manage their transplant.